Economic Environment in Latvia: Interaction of Ethical and Ethnic Values in Organizational Culture - Volkov, Vladislav (Środowisko gospodarcze na Łotwie: interakcja wartości etycznych i etnicznych w kulturze organizacyjnej, 2023)
The article shows the importance of studying the economic environment and the organizational culture in Latvia as an ethnically diverse aspect, taking into account the influence of the ethnic factor. To confirm the hypothesis that the ethnic factor also plays an importantrole in the economic life of Latvia, the article written in 2021 organized a sociological study in the research project “Interaction of the individual, society and the state in the overall process of Latvian history: conflicts of values and the formation of common values at historical breaking points”. As a key indicator of the integrity of organizational culture for the multi-ethnic environment of Latvia, the author chose the value of universal moral norms, primarily justice, to regulate relations between ethnic Latvians and Russians. The data of this study showed that a high assessment of the ideals of justice is characteristic of the moral consciousness of both ethnic Latvian and Russian respondents. At the same time, the attitude towards the implementation of these ideals, in economic behavior, business communication has some differences among representatives of these ethnic groups.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2023; vol. 67, nr 3, s. 100-108
Keywords: organizational culture; multi-ethnic environment; ethical values; ethnic favouritism; kultura organizacyjna; środowisko wieloetniczne; wartości etyczne; faworyzowanie etniczne